2019
DOI: 10.3390/molecules24050896
|View full text |Cite
|
Sign up to set email alerts
|

Laxative Effect of Spicatoside A by Cholinergic Regulation of Enteric Nerve in Loperamide-Induced Constipation: ICR Mice Model

Abstract: Researches on spicatoside A (SpiA)-containing natural products suggest the possibility of SpiA as a potential laxative to alleviate chronic constipation. However, no studies have been conducted with single compound administration of SpiA. To verify the laxative effects and mechanism of action of SpiA on chronic constipation, we investigated alterations in the excretion parameters, histological structure, and cholinergic regulation of the enteric nerve in the colons of Institute of Cancer Research (ICR) mice wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 32 publications
3
20
0
Order By: Relevance
“…Kovacic et al (54) performed a clinical study using auricular neurostimulation for treating GI disorders in adolescents and reported that its effects were related to vagal efficiency (55). Our previous studies (31,34) reported that loperamide reduced vagal activity via the autonomic-cholinergic function while other studies (56,57) showed inhibitory effects of loperamide on enteric neurons and ICC, similar to the findings in the present study. To further explore whether aVNS was involved in the vagal efferent pathway in loperamide-induced constipated rats, we analyzed the ECG, neural and ICC changes in the ENS.…”
Section: Discussionsupporting
confidence: 88%
“…Kovacic et al (54) performed a clinical study using auricular neurostimulation for treating GI disorders in adolescents and reported that its effects were related to vagal efficiency (55). Our previous studies (31,34) reported that loperamide reduced vagal activity via the autonomic-cholinergic function while other studies (56,57) showed inhibitory effects of loperamide on enteric neurons and ICC, similar to the findings in the present study. To further explore whether aVNS was involved in the vagal efferent pathway in loperamide-induced constipated rats, we analyzed the ECG, neural and ICC changes in the ENS.…”
Section: Discussionsupporting
confidence: 88%
“…The immunoreactive expression for PGP9.5 was significantly lower in the myenteric and submucosal plexus of BDNF-/- mice with slow gut motility [ 6 ]. The lop-induced constipation institute of cancer research (ICR) and Sprague Dawley (SD) model showed a decrease in two ICC markers (C-kit and SCF), an increase in two enteric-nerve-related factors (transient receptor potential vanilloid 1 (TRPV1) and NOS), and a decrease in the other enteric-nerve-related factors (PGP9.5, Brain-derived neurotrophic factor (BDNF), and GNDT) [ 43 , 44 ]. In a few studies, however, the density and distribution of ICC in patients with slow transit constipation were not significantly different from normal colon [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that Cajal bodies (ICC), which have an abnormal number of mesenchymal cells, can cause changes in the cell morphology and network structure, which can slow down colonic peristalsis and induce constipation, which may be the basic pathogenesis of slow transit constipation. 48,49 c-Kit is one of the specic markers of ICC, and is a factor in maintaining ICC proliferation and growth under normal conditions, 50 SCF is a natural ligand of the c-Kit receptor. 51 Studies have found that the concentration of SCF is very important to the cultivation of the ICC.…”
Section: Discussionmentioning
confidence: 99%